An evaluation and enhancement approach of the carbon footprints-based environmentally sustainable service competitiveness for coffee shops. (2016) - Chiang, Tzu-An; Wang, Shen-Tsu
This paper develops an evaluation and enhancement approach of the carbon footprints (CFs) based environmentally sustainable service competitiveness for coffees shops. Firstly, the proposed approach uses the service blueprint to analyse the service process of coffee shops and the working times of the required direct facilities and the supporting facilities to estimate the amounts of greenhouse gas (GHG) emissions. By using data envelopment analysis, the holistic performance evaluation model of environmentally sustainable service operation for coffee shops is created to find the non-benchmark environmentally sustainable service coffee shops. To improve environmentally sustainable service performance of the non-benchmark coffee shops, this paper evaluates the environmentally sustainable performance evaluation models of the meal-ordering and cooking areas and dining areas. Finally, this research gives an in depth analysis to comprehend the decreasing amount of the CF of each facility in the non-benchmark environmentally sustainable service areas.